The Determinants and Impact of Mandatory Disclosure In Indonesian Manufacturing Companies - Andian Ari Istiningrum; Muhammad Zaky Za'im Muhtadi (Journal of Economics, Business, and Accountancy Ventura, 2018)
The primary objective of this research is to determine the factors that have an association with mandatory disclosure and stock return. This research investigated 47 manufacturing companies listed on the Indonesia Stock Exchange in 2012. Mandatory disclosure in this research used items required to be disclosed under IAS 16 and IAS 17. The data analysis used the path analysis by setting two structural equation models. The Sobel Test was used to determine whether mandatory disclosure functions as a mediator. The research proved a significantly positive association of company age with the mandatory disclosure in contrast to company size and company profitability. This implies that the investors are able to find complete and transparent information in the financial statement of mature manufacturing companies.Â  Moreover, company size, company profitability, and mandatory disclosure have a significant positive association with stock return. This implies that it is necessary for the companies to disclose information as required by the accounting standard in Indonesia and the investors may recognize the big and the high profitability manufacturing companies as the places to invest. However, mandatory disclosure does not function as a mediator between company size, company age, company profitability and stock return.